Contingency management for college student smokers: The role of drinking as a moderator and mediator of smoking abstinence during treatment. (May 2018) - Cassidy, Rachel N.; Jackson, Kristina M.; Rohsenow, Damaris J.; Tidey, Jennifer W.; Tevyaw, Tracy O'.L.; Barnett, Nancy P.; Monti, Peter M.; Miller, Mollie E.; Colby, Suzanne M.
Abstract: Introduction: Contingency management (CM) is effective for promoting smoking abstinence; however, moderators and mediators of CM treatment efficacy in young adult populations are under-explored. We leveraged fine-grained data from a large randomized controlled trial: 1) to determine whether early attainment of sustained abstinence mediated the effect of treatment on abstinence; 2) to test whether heavy drinking moderated the effect of treatment on abstinence; and 3) to test a serial mediation model of the effects of drinking during early treatment on sustained smoking abstinence. Methods: College student smokers (N = 110) were randomized to receive either CM treatment or noncontingent reinforcement (NR) over a 21-day treatment period. All participants received 5 for providing twice-daily breath carbon monoxide (CO) samples. In CM, additional money was provided for samples that indicated smoking reduction (Initial Phase; first 7 days), and for samples ≤ 5 ppm (Abstinence Phase; following 14 days). Results: CM treatment led to greater sustained abstinence relative to NR. Longer sustained abstinence in the Initial Phase partially mediated the effect of treatment on sustained abstinence in the Abstinence Phase. Heavier pretreatment drinkers had shorter periods of sustained abstinence in the Abstinence Phase; this effect was greater in CM. A serial mediation model determined that increased drinking during the Initial Phase led to decreased sustained abstinence, which then led to decreased sustained abstinence in the Abstinence Phase. Conclusions: These data provide a greater understanding of how heavy drinking and early sustained abstinence may affect success during treatment in young adults undergoing contingency management treatment for smoking. Highlights: Improving smoking cessation rates in young adults is important for the future health of young people. We found that early sustained abstinence improved later sustained abstinence in contingency management (CM). Heavy drinking both before and during CM treatment undermined sustained abstinence. CM holds promise for young smokers, but drinking needs to be addressed concurrently.